2021
DOI: 10.1159/000511986
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and Lack of Joy Are Related to Physical Frailty among Northern Japanese Community-Dwellers from the ORANGE Cohort Study

Abstract: <b><i>Introduction:</i></b> A prevalence of frailty is gradually increasing with the progress of aging in Japan, and critical challenges regarding early diagnosis and prevention of frailty were necessary in community. Although previous studies have well documented the characteristics of physical disability, there is limited information on frail state differences among older adults in Japanese rural areas. The aim of our cross-sectional observational study was to clarify the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…All of these consequences tend to promote or heighten frailty. In line with the above information, there are certain studies that conclude that the lack of joy and the presence of a negative attitude towards ageing can function as risk factors for frailty [43,44]. Our findings show that the presence of a psychopathology doubles the odds of an older person presenting pre-frailty.…”
Section: Discussionsupporting
confidence: 89%
“…All of these consequences tend to promote or heighten frailty. In line with the above information, there are certain studies that conclude that the lack of joy and the presence of a negative attitude towards ageing can function as risk factors for frailty [43,44]. Our findings show that the presence of a psychopathology doubles the odds of an older person presenting pre-frailty.…”
Section: Discussionsupporting
confidence: 89%
“…The NCGG-FAT has been reported to be highly reliable and valid compared to traditional neurocognitive scales [ 23 ]. The NCGG-FAT has been used in previous studies with community-dwelling older adults [ 8 , 25 , 26 , 27 ]. Physical frailty was defined using the five components suggested by Fried: slowness, weakness, exhaustion, low physical activity and weight loss [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, some evidence of a relationship with depression has also been observed, but this association appears to be weaker and is less commonly reported [45][46][47]. An association has also been reported between mental pathology and frailty [48,49]. It has been observed that persons with a psychopathology tend to be less physically active, to have a less active social life, and to consume a less healthy diet, and that any or all of these factors could be related to a loss of strength and muscle mass.…”
Section: Discussionmentioning
confidence: 99%